2017
DOI: 10.1083/jcb.201607085
|View full text |Cite
|
Sign up to set email alerts
|

The Rab7 effector PLEKHM1 binds Arl8b to promote cargo traffic to lysosomes

Abstract: Rab7 and Arl8b mediate vesicle transport and fusion with lysosomes. Marwaha et al. show that the Rab7 effector PLEKHM1 competes with PLEKHM2/SKIP for binding to Arl8b and that Arl8 mediates recruitment of the HOPS complex to PLEKHM1-positive vesicles for fusion, suggesting that Arl8b and its effectors orchestrate lysosomal transport and fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
145
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(153 citation statements)
references
References 37 publications
4
145
3
Order By: Relevance
“…To study transport route selectivity operational on endolysosomes, we examined the interplay between their associated GTPases, Rab7, and Arl8b. In agreement with previous findings (Marwaha et al , ), we noted that part of the repertoire populated by Rab7 also carries Arl8b (Fig A and B). It has been speculated that Arl8b marks a later maturation stage as compared to Rab7 (Hofmann & Munro, ; Garg et al , ), and we therefore considered whether Rab7 activity status affects localization and behaviour of Arl8b.…”
Section: Resultssupporting
confidence: 94%
“…To study transport route selectivity operational on endolysosomes, we examined the interplay between their associated GTPases, Rab7, and Arl8b. In agreement with previous findings (Marwaha et al , ), we noted that part of the repertoire populated by Rab7 also carries Arl8b (Fig A and B). It has been speculated that Arl8b marks a later maturation stage as compared to Rab7 (Hofmann & Munro, ; Garg et al , ), and we therefore considered whether Rab7 activity status affects localization and behaviour of Arl8b.…”
Section: Resultssupporting
confidence: 94%
“…In addition, Rab7 is still required for LE-lysosome fusion in Drosophila [79,86]. This suggests that Rab7 may assist in the tethering process, perhaps by recruiting the conserved LE/lysosomal adaptor PLEKHM1 (FlyBase Annotation Symbol CG6613) which is strongly precipitated by activated Drosophila Rab7 [48] and in mammals facilitates LE-lysosome fusion [87,88]. …”
Section: Discussionmentioning
confidence: 99%
“…To confirm the effect of Arl8b on lysosome motility, we decreased the cytoplasmic pH of control- and Arl8b- siRNA treated HeLa cells from pH 7.2 to 6.5. Previous studies have demonstrated that lysosomes traffic toward the plasma membrane in response to acidic pH (34, 41, 43). At pH 7.2 control siRNA transfected cells showed a normal perinuclear distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Based on which effector Arl8b binds (HOPS complex, PLEKHM1 or SKIP/Kif5b), it can control the delivery of endocytosed material to lysosomes (29, 3132, 3435) or control lysosome and lysosome-related organelle motility toward the cell periphery, respectively (3637). Rosa-Ferreira et al identified SKIP and kinesin-1 as Arl8b binding-partners in directing conventional lysosomes to the cell periphery (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation